A common challenge in older adults: Classification, overlap, and therapy of depression and dementia. Issue 1 (28th September 2016) - Leyhe, Thomas; Reynolds, Charles F.; Melcher, Tobias; Linnemann, Christoph; Klöppel, Stefan; Blennow, Kaj; Zetterberg, Henrik; Dubois, Bruno; Lista, Simone; Hampel, Harald
Abstract: Late‐life depression is frequently associated with cognitive impairment. Depressive symptoms are often associated with or even precede a dementia syndrome. Moreover, depressive disorders increase the risk of persistence for mild cognitive impairment and dementia. Here, we present both the current state of evidence and future perspectives regarding the integration and value of clinical assessments, neuropsychological, neurochemical, and neuroimaging biomarkers for the etiological classification of the dementia versus the depression syndrome and for the prognosis of depression relating to dementia risk. Finally, we summarize the existing evidence for both pharmacotherapy and psychotherapy of depression in demented patients. There is an urgent need for large‐scale collaborative research to elucidate the role and interplay of clinical and biological features in elderly individuals with depressive disorders who are at elevated risk for developing dementia. To overcome barriers for successful drug development, we propose the introduction of the precision medicine paradigm to this research field.